Meeting the challenge of population ageing. (5th October 2009) - Doyle, Yvonne; McKee, Martin; Rechel, Bernd; Grundy, Emily
Abstract : Increased longevity poses a challenge to the welfare state, but the problems can be overcome, argue Yvonne Doyle and colleagues